Situation Report: Czechoslovakia, 22 November 1985 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Brandt's Visit to Czechoslovakia The Riddle of the Federal Minister of Finance Relations with the West After the Mass Pilgrimages The Communist Cadres in the Age of Intensification The Problems of Economic Integration